Student Responses to The Application of The Number Head Together Learning Model in Physics Subjects - Jufrida, J; Astalini, A; Darmaji, D; Tanti, T; Kurniawan, D A; Erika, E; Hayi, R; Sukarni, W (Jurnal Pendidikan Fisika Indonesia, 2021)
The NHT (Number Head Together) learning model is a learning model that has a structure designed to influence student interaction patterns. The NHT learning model emphasizes students to work together in finding, processing, and reporting information. This model can make students more communicative during the physics learning process. The use of conventional learning models will generally make students bored and uninterested in learning physics. In physics subjects, teachers generally use conventional learning modelsStudents' boredom will arise when learning using conventional models. The purpose of this study was to describe students' responses to the application of the NHT type cooperative learning model. The benefit of this research is to know the student's response to the application of the NHT type of cooperative learning model, as well as the application of the NHT type of cooperative learning model in physics learning. This study used a mixed method research design. The data in this study were analyzed using the triangulation method. Data were collected through interviews, observation, and documentation. The subjects in this study were high school students. The results showed that some respondents responded quite well to the application of the NHT type of cooperative learning model in physics learning, and some of them responded well to the application of the NHT type of cooperative learning. In learning physics, the use of learning models affects the continuity of the teaching and learning process which will have an impact on the knowledge and learning outcomes possessed by students.